Porous hexagonal nanoplate cobalt oxide derived from a coordination polymer as an effective catalyst for activating Oxone in water. (December 2020) - Tuan, Duong Dinh; Hung, Ching; Da Oh, Wen; Ghanbari, Farshid; Lin, Jia-Yin; Lin, Kun-Yi Andrew
Abstract: As cobalt (Co) represents an effective transition metal for activating Oxone to degrade contaminants, tricobalt tetraoxide (Co3 O4 ) is extensively employed as a heterogeneous phase of Co for Oxone activation. Since Co3 O4 can be manipulated to exhibit various shapes, 2-dimensional plate-like morphology of Co3 O4 can offer large contact surfaces. If the large plate-like surfaces can be even porous, forming porous nanoplate Co3 O4 (PNC), such a PNC should be a promising catalyst for Oxone activation. Therefore, a facile but straightforward method is proposed to prepare such a PNC for activating Oxone to degrade pollutants. In particular, a cobaltic coordination polymer with a morphology of hexagonal nanoplate, which is synthesized through coordination between Co 2+ and thiocyanuric acid (TCA), is adopted as a precursor. Through calcination, CoTCA could be transformed into hexagonal nanoplate-like Co3 O4 with pores to become PNC. This PNC also shows different characteristics from the commercial Co3 O4 nanoparticle (NP) in terms of surficial reactivity and textural properties. Thus, PNC exhibits a much higher catalytic activity than the commercial Co3 O4 NP towards activation of Oxone to degrade a model contaminant, salicylic acid (SA). Specifically, SA was 100% degraded by PNC activating Oxone within 120 min, and the E a of SA degradation by PNC-activated Oxone is 70.2 kJ/mol. PNC can also remain stable and effective for SA degradation even in the presence of other anions, and PNC could be reused over multiple cycles without significant loss of catalytic activity. These features validate that PNC is a promising and useful Co-based catalyst for Oxone activation. Highlights: A coordination polymer nanoplate of Co and thiocyanuric acid (CoTCA) is synthesized. CoTCA is transformed into porous nanoplate Co3 O4 (PNC) for activating Oxone. PNC exhibits more reactive and larger contact surfaces than commercial Co3 O4 NPs. PNC shows higher catalytic activity than pristine Co3 O4 NPs for activating Oxone. Emerging contaminant, salicylic acid, can be efficiently degraded by PNC-activated Oxone.